Awareness, attitude, and practice of pediatricians regarding early childhood caries and infant oral healthcare of children in Puducherry- A cross-sectional survey - G S Prathima; Muthukrishnan Kavitha; Gurusamy Kayalvizhi; Adimoulame Sanguida; Mohandoss Suganya; Selvabalaji Arumugam (Wolters Kluwer Medknow Publications, 2020)
Context: Early Childhood Caries (ECC) is the most virulent form of caries, which requires early intervention. Pediatricians are health professionals who first examine the child, and must be able to educate parents about basic preventive dental care, early diagnosis of pathological changes in the oral cavity and appropriate referrals for the children. Aims: To assess the awareness, attitude, and practice among pediatricians regarding ECC and Infant Oral Healthcare (IOHC) in Puducherry. Settings and Design: Setting: Study was conducted among pediatricians of Puducherry. Design: Observational Cross-sectional study. Methods and Material: After obtaining consent from Pediatricians, a prevalidated questionnaire was distributed and collected from them regarding their awareness, attitude, and practices toward ECC and IOHC. Statistical Analysis Used: Percentage. Results: Out of 85% Pediatricians who responded, 57% of them were aware of initial white spot lesions, and 39% of them were aware of maternally-derived Streptococcus mutans disease. 100% of them were willing to avail information, training on IOHC. Conclusions: It is clear from the study that Pediatricians in Puducherry had limited awareness regarding the prevention of oral diseases. It is essential to provide sufficient knowledge to them by incorporating a module on ECC and infant oral health care in their curriculum.